Correlations of vascular cognitive impairment with brain-derived neurotrophic factor and trace elements - Zhou, Rong; Lei, Chao; Zhi, Haiyang (Revista română de medicină de laborator, 2025)
NOABSTRACTCognitive impairment has become one of the major public health problems due to population aging and the increased morbidity associated with stroke. In this study, we aimed to analyze the correlations of vascular cognitive impairment (VCI) with brain-derived neurotrophic factor (BDNF) and trace elements.Between January 2022 and January 2024, a total of 206 subjects were included in the study, of which 103 were VCI patients treated in our hospital (a cognitive impairment group), and 103 were volunteers undergoing physical examination (a control group). Comparisons were conducted on the levels of BDNF and trace elements (Cu, Fe, Zn, Ca, Mg, Se, As, and Al) between the two groups.In comparison with the control group, the cognitive impairment group had significantly reduced levels of BDNF, Cu, Fe and Zn (p<0.05), a significantly raised Al level (p<0.05), and decreases in the total score of Mini-Mental State Examination (MMSE) and corrected total score of Montreal Cognitive Assessment (MoCA) (p<0.05). The total score of MMSE and corrected total score of MoCA were positively correlated with the levels of BDNF, Cu, Fe, and Zn (p<0.05) and negatively correlated with the Al level in both groups (p<0.05). BDNF <5.39 μg/L, Cu <10.87 μmol/L, Fe <5.97 μmol/L, Zn <77.32 μmol/L, and Al >0.72 μmol/L were risk factors for VCI.VCI patients have significantly lower levels of BDNF and trace elements (Cu, Fe, and Zn) and a significantly higher Al level than those of healthy populations. Excessively low levels of BDNF and trace elements (Cu, Fe, and Zn) and an overly high level of harmful element Al are risk factors for VCI.